Subi Shahs Holistic theory of Nepali performing arts: implications for research and teaching - Stirr, Anna Marie (Tanjong Malim, 2021)
Subi Shahs Holistic theory of Nepali performing arts: implications for research and teaching by Stirr, Anna Marie